The Impact of Financial Inclusion and Islamic Fintech on the Challenges of the SDGs (Sustainable Development Goals) - Mufaidah, Mufaidah (Budapest International Research and Critics University, 2022)
Islamic fintech has the potential to encourage financial inclusion by meeting the needs of the non-bankable market segment. Therefore, the role of fintech in accelerating financial inclusion for the community is very significant because fintech has various approaches to assessing creditworthiness or financing for its customers. the role of financial inclusion will lead to the achievement of the challenges of the Sustainable Development Goals (SDGs). Poverty alleviation is one of Indonesia's development priorities. This is in line with the first commitment to the Sustainable Development Goals (SDGs), namely reducing poverty and hunger. The results show that Islamic Fintech and financial inclusion have a significant influence on the SDGs.